THE ANTINOMIES OF HABERMAS’RECONSTRUCTION OF HISTORICAL MATERIALISM: Towards A Dialectical Renewal of Critical Social Theory’s Historical Perspective - Browne, Craig (Revista Inter-Legere, 2019)
There are few attempts to reformulate the historical perspective of classical sociological theory comparable to that of Jürgen Habermas’ reconstruction of historical materialism. Habermas considered historical materialism to be principally a theory of social evolution and he sought to revise its conception of historical development. In Habermas’ opinion, the logic of the development of normative structures, social identities and cultural understandings differs from that of material production and the organizational complexity of social systems. My analysis reveals how the major innovation of Habermas’ reconstruction of historical materialism is the ensuing conceptualizations of the social relations of production as forms of social integration and the function of systematically distorted communication in their historical institution. Despite the significant implications of this supplementation of the paradigm of production with a theory of communication, Habermas’ reconstruction of historical materialism is shown to be limited by its inflexible logic of development and disengagement from the conflicts internal to processes of material production. It is proposed that the historical perspective of other strands of contemporary social theory may rectify these limitations through their concern with social creativity, institutional variations and the dialectics of social struggle.